Diagnostic performance of T1 and T2 mapping to detect intramyocardial hemorrhage in reperfused ST-segment elevation myocardial infarction (STEMI) patients - Bulluck, H (John Wiley and Sons Inc., 2020)
10.1002/jmri.25638